(untitled) (Bangladesh Journal of Microbiology, 2016)
Pollution of the environment with toxic heavy metals is spreading throughout the world along with industrial progress. Removal of these toxic heavy metals by using bacteria has achieved growing attention in recent years. The present study focuses on isolation of lead and chromium tolerant Bacillus spp., from the Buriganga and the Shitalkhya, the two major rivers surrounding Dhaka. A total of 25 Bacillus spp. isolates tolerant to 50 ppm lead and chromium were preliminarily identified based on morphological and biochemical analysis. Further investigation revealed that all isolates were also able to grow at 1000 ppm lead and 400 ppm chromium, while tolerance to 1500 ppm lead and 500 ppm chromium was observed among 48% and 76% isolates, respectively. All isolates were also able to grow at 50 ppm copper and 50 ppm zinc, while 72% grew at 100 ppm copper. The heavy metal tolerant Bacillus spp were also multi drug resistant and showed resistance to Tetracycline (100%), Ceftazidime (100%), Ceftriaxone (100%), Ampicillin (28%) and Nalidixic acid (24%). Bangladesh J Microbiol, Volume 30, Number 1-2,June-Dec 2013, pp 17-22